Progressive reflective practices of pre-service teachers of English through the process of action research - Lee, Seung Chun (2011)
This article focuses on the development of reflective practices in a supervisory project carried out by the student teachers of English at a national university of Malaysia, where action research has been used as a teacher development strategy towards teacher autonomy.This paper aims at providing an account of how student teachers move along a continuum of three levels of reflective practice (surface reflection, pedagogical reflection, and critical reflection) to become critically reflective teachers through the experience of keeping a reflective journal in the action research project. The analysis is three-dimensional: First, student teachers were asked to write their thoughts about the action research seminar, the action research project, and English classroom experiences on a weekly basis (two entries in a week); Secondly, student teachers were given an open-ended questionnaire with several questions on action research in the first and last sessions in order to investigate the role of action research within critical teacher education towards teacher autonomy; Lastly, the contribution action research can make to the professional development of teachers as reflective practitioners will also be discussed in the light of the experience of supervision.